First report of airborne pollen in Santa Rosa, La Pampa, Argentina: A 2-year survey - Caramuti, Valeria (2014)
The aim of this study was to determine the qualitative and quantitative composition of the airborne pollen of Santa Rosa city, La Pampa (Argentina), and to analyse the seasonal behaviour of the pollen types that have the highest representation in the atmosphere. The city, with temperate climate, is located in a cultivated area that corresponds phytogeographically to a xerophytic forest limiting with grasslands. The pollen sampling was performed using a Hirst-type volumetric spore trap located in the urban centre of the city, 15 m above ground level, from July 2007-June 2009. The annual pollen index was 51,647 pollen grains. The airborne pollen consisted of 73 pollen types, 42 of woody origin represented 66 % of the total and with winter-spring seasonality and 31 were of herbaceous origin, which represented 30 % of the total and with spring-summer seasonality. The composition of the woody airborne pollen reflected the formation of urban vegetation, consisting mainly of exotic taxa from tree species used in urban tree alignment. The most abundant types were as follows: Cupressaceae, Fraxinus, Ulmus, Olea europaea, Styphnolobium japonicum, Myrtaceae, Pinaceae, Platanus, Celtis- Morus and Populus. Native components such as Condalia microphylla were also found, indicating the 'Espinal' phytogeographical province that was typical of the area. The most abundant herbaceous airborne pollen types, in descending order, were as follows: Poaceae, Amaranthus-Chenopodiaceae, Urticaceae, Brassicaceae and Asteraceae. The emission sources of these pollen types were weeds that grew spontaneously in parks, waste grounds and flower beds of the city.